If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 + 3x = -36 + 6x Solving -26 + 3x = -36 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -26 + 3x + -6x = -36 + 6x + -6x Combine like terms: 3x + -6x = -3x -26 + -3x = -36 + 6x + -6x Combine like terms: 6x + -6x = 0 -26 + -3x = -36 + 0 -26 + -3x = -36 Add '26' to each side of the equation. -26 + 26 + -3x = -36 + 26 Combine like terms: -26 + 26 = 0 0 + -3x = -36 + 26 -3x = -36 + 26 Combine like terms: -36 + 26 = -10 -3x = -10 Divide each side by '-3'. x = 3.333333333 Simplifying x = 3.333333333
| 5-3x=7x+5 | | 102=5w+17 | | -9(x-4)=-3x+42 | | 12-2x=2x+8 | | X=8-3(-3) | | A=10x+y+2 | | 21+3x=56 | | -9x-4y=-4 | | -x=-3+2x | | 210p=1890 | | 3x-5=12+3x | | 6n+10=-4n+50 | | 8*n=32 | | 16x^2-27e=0 | | 10=6x+3 | | 9x+11=6x+-9+3 | | 3x-18=12+7x | | 4x-4x+5=12 | | 4+5(x-2)=6+7(x-2) | | (10-2x)(8-2x)(x)=f(x) | | -8+x=4x+1 | | cos+2sec=-3 | | -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 | | =(4x-3)(2x+7)-(4x-3)(6-x) | | 3(a+b)+2(a-b)= | | 0.1x+0.25x=20.65 | | -3=153 | | 2v-26=-9(v+9) | | 9x-10=2x+6 |